The mediating role of perceived administrative support for the effect of job motivation on organizational identification - Gökçe Özdemir (International Journal of Evaluation and Research in Education (IJERE), 2020)
In this study, the mediating role of perceived administrative support for the effect of teachers’ job motivation on their organizational identification perceptions was investigated. For this purpose, in mind, the opinions of 320 kindergarten teachers in 304 schools from 13 different school districts of Şahinbey/Gaziantep were received. However, 233 scales were taken into consideration. The research data were collected through Job Motivation Scale (JMS), Organizational Identification Scale (OIS) and Perceived Administrative Support Scale (PASS). Descriptive statistics, correlation analysis, multiple regression analysis, and path analysis were used in data analysis. Analysis results revealed that the job motivation perceptions of teachers were high. In addition, it was revealed that the participants also had high scores for organizational identification and perceived administrative support. Correlation analyses yielded positive, moderate and significant relationships between the research variables. Path analysis uncovered that perceived administrative support had a “partial mediating” role for the relationship between job motivation and organizational identification. Based on research findings, it was concluded that the effect of job motivation on teachers’ identification with their organizations was realized through perceived administrative support, albeit partially.